2012
DOI: 10.1111/j.1439-0272.2012.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of curcumin against acute cadmium toxicity on male reproductive system in rats

Abstract: The aim of the present study was to investigate the ameliorative effect of curcumin (CMN) against acute cadmium chloride (CdCl(2)) toxicity on male reproductive system in rats. CdCl(2) is known to be a heavy metal and potential environmental pollutant. For this purpose, 28 rats were equally divided into four groups; the first group was kept as control and given distilled water and corn oil as carrier. In second and third groups, CdCl(2) and CMN were administered at the dose with 1 mg kg(-1) day(-1) and 100 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 23 publications
3
55
0
Order By: Relevance
“…Many studies have shown that curcumin as a free radical scavenger inhibits nitric oxide and reactive oxygen species (ROS) production in macrophages, especially in testicular tissue. So it is believed that Curcumin may stop peroxidative alteration in the sperm and the testicular membrane which leads to enhancement of sperm motility and decrease in spermatozoa defects (Oguzturk et al, 2012;Noorafshan & Ashkani-Esfahani, 2013). The effects of Curcumin on varicocele have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that curcumin as a free radical scavenger inhibits nitric oxide and reactive oxygen species (ROS) production in macrophages, especially in testicular tissue. So it is believed that Curcumin may stop peroxidative alteration in the sperm and the testicular membrane which leads to enhancement of sperm motility and decrease in spermatozoa defects (Oguzturk et al, 2012;Noorafshan & Ashkani-Esfahani, 2013). The effects of Curcumin on varicocele have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Eight weeks after surgery, group T rats received 100 mg/kg of Curcumin (Oguzturk et al) (Sigma/ Aldrich Chemical Co.) for 8 weeks. The drug was dissolved in corn oil (Farombi et al, 2007;Oguzturk et al) and was immediately administered via gavage techniques. The sperm parameters of groups V1 and V2 were evaluated 8 and 16 weeks after surgery respectively and groups T and Sh were evaluated 16 weeks after varicocele induction (8 weeks after treatment).…”
Section: Methodsmentioning
confidence: 99%
“…Th e eff ect of the curcumin against acute cadmium chloride (CdCl 2 ) toxicity on the reproductive system in male rats has been investigated (Oguzturk et al 2012). CdCl 2 led to a signifi cant increase in oxidative stress.…”
Section: Th E Eff Ect Of C Longa and Curcumin On Male Reproductive Smentioning
confidence: 99%
“…In addition, CdCl 2 administration resulted in vacuities, edema, hemorrhage, and acute infl ammatory cells infi ltration in the interstitial space. Administration of curcumin aft er CdCl 2 toxicity reduced the severity of histopathological changes (Oguzturk et al 2012).…”
Section: Th E Eff Ect Of C Longa and Curcumin On Male Reproductive Smentioning
confidence: 99%
“…There are several studies in in vitro and rodent models which show that curcumin protects against Cd-induced immunotoxicity (Pathak and Khandelwal 2008;Alghasham et al 2013), nephrotoxicity (Deevika et al 2012), neurotoxicity (Daniel et al 2004), lung toxicity (Rennolds et al 2012), reproductive toxicity (Aktas et al 2012;Oguzturk et al 2012), hepatoxicity (Eybl et al 2004;Tarasub et al 2012;Garcia-Nino and Pedraza-Chaverri 2014), and cardiovascular toxicity . The data acquired from our experiments provide evidence that curcumin has a significant ability to protect against vascular dysfunction induced by Cd in mice .…”
Section: Mitigation Of Cadmium Toxicity With Curcumin and Tetrahydrocmentioning
confidence: 99%